IMPLEMENTASI MODEL PEMBELAJARAN 5E UNTUK MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA - Saiful Prayogi; Samsun Hidayat; Armansyah Armansyah (Universitas Pendidikan Mandalika, 2013)
This study aims to improve learning outcomes and critical thinking skills of students SMPN 18 Mataram Academic Year 2012/2013 through the implementation of 5E learning model. The type of research used is classroom action research (PTK). This research is conducted in a cycle consisting of planning, implementation, observation, and reflection. Data on cognitive learning outcomes were obtained from multiple choice tests and critical thinking skills using critical thinking skills tests. The subjects of the research are students of class VIII-A which is 19 people. The results showed that there was an increase in learning outcomes and critical thinking skills due to the 5E learning model. In the first cycle of classical completeness cognitive learning outcomes is 94% and the average value of 82 is categorized completely. Furthermore, critical thinking ability in the first cycle is worth an average of 76 that is completely categorized. It can be concluded that the 5E learning model has been able to improve learning outcomes and students' creative thinking ability.